2021
DOI: 10.1111/ppc.12855
|View full text |Cite
|
Sign up to set email alerts
|

The relationship among aging in place, loneliness, and life satisfaction in the elderly in Turkey

Abstract: Purpose This study was conducted to determine the relationship between aging in place, loneliness, and life satisfaction in older people. Design and Methods The descriptive and cross‐sectional study has used the Aging in Place Scale (APS), the Life Satisfaction Scale (LSS), and the Loneliness Scale for the Elderly (LSFE). The study was examined the correlation among APS, LSS, and LSFE. Finding In our study, when we examined the subscales of the APS scale, we found that the perceived social support, physical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
(47 reference statements)
0
5
0
1
Order By: Relevance
“…On the other hand, studies, such as the one in [ 51 ], report on how, for “most elderly people living at home, [...] their satisfaction with their immediate surroundings increased, their life satisfaction improved, and loneliness reduced” . Likewise, the studies in [ 52 , 53 ] suggest the beneficial impact that age-in-place has in avoiding social isolation and perceived loneliness in older adults.…”
Section: Literature Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, studies, such as the one in [ 51 ], report on how, for “most elderly people living at home, [...] their satisfaction with their immediate surroundings increased, their life satisfaction improved, and loneliness reduced” . Likewise, the studies in [ 52 , 53 ] suggest the beneficial impact that age-in-place has in avoiding social isolation and perceived loneliness in older adults.…”
Section: Literature Landscapementioning
confidence: 99%
“…In this regard, and specifically concerning older adult’s social isolation and loneliness, we could think about mixed (socio-spatial and technological) solutions to which studies suggest: if the perceived and achievable social support, together with the physical competence, are highly maintained, then the loneliness feeling decreases [ 51 , 60 , 61 ], regardless of whether the older adult lives independently or in an institution.…”
Section: Literature Landscapementioning
confidence: 99%
“…Life satisfaction re ects the comparison between one's life expectations and actual life situation [18,19]. As an important indicator of subjective well-being, it also plays an important role in people's lives [20]. Previous studies have found that grandparenting is signi cantly associated with grandparents' life satisfaction.…”
Section: Grandparenting and Life Satisfactionmentioning
confidence: 99%
“…Bu çalışmada kadınların erkeklerden, evli olmayanların evlilerden ve üniversite mezunu olanların diğer eğitim düzeyindeki yaşlılara göre yalnızlık düzeyinin düşük olduğu bulunmuştur. Çalışmamızla tutarlı olarak bazı çalışmalarda yaşlı erkeklerde kadınlara göre yalnızlık düzeyinin daha fazla [29,30], bazı çalışmalarda kadınlarda erkeklerden [31,32], bazı çalışmalarda ise cinsiyete göre herhangi bir farklılık olmadığı belirtilmektedir [33][34][35]. Yalnızlık durumu bireylere göre değişiklik gösterse de kadınların; iletişim kurma, sosyalleşme rollerini erkeklere göre daha kısa sürede ortaya koymalarının kadınların yalnızlık puanını etkilediği düşünülebilir.…”
Section: Tartışma Ve Sonuçunclassified